2011
DOI: 10.1093/bja/aer274
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative maintenance or interruption of aspirin on thrombotic and bleeding events after elective non-cardiac surgery: the multicentre, randomized, blinded, placebo-controlled, STRATAGEM trial

Abstract: In these at-risk patients undergoing elective non-cardiac surgery, we did not find any difference in terms of occurrence of major thrombotic or bleeding events between preoperative maintenance or interruption of aspirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(79 citation statements)
references
References 33 publications
0
73
0
6
Order By: Relevance
“…Although the power is limited, there is no significant difference between two groups, according to age, sex, operation, and study period. To our knowledge, the only randomized study, conducted for all types of surgery, had to be prematurely stopped due to the insufficient patient inclusions (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the power is limited, there is no significant difference between two groups, according to age, sex, operation, and study period. To our knowledge, the only randomized study, conducted for all types of surgery, had to be prematurely stopped due to the insufficient patient inclusions (1).…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies as well as a prospective randomized trial [1] have shown that the interruption of APT was associated with an increased risk of thrombosis. Moreover, APT maintenance was not associated with a significantly higher hemorrhagic risk.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these studies recommended discontinuation of dual antiplatelet therapy and continuation of a single agent. Since prior studies have shown that aspirin may not increase the risk of bleeding complications to the extent that clopidogrel does, it may be safest to recommend continuation of aspirin alone in these patients [22].…”
Section: Video-assisted Thoracic Surgerymentioning
confidence: 99%
“…RCTs showed mixed results but with a potential decreased risk of vascular events in patients on ASA in the perioperative period [46][47][48]. In contrast, the PEP trial, involving 13 356 patients undergoing hip surgery, demonstrated more cardiac ischaemic events (death due to ischaemic heart disease or nonfatal MI) in patients randomised to ASA versus placebo (HR 1.33, 95% CI 1.00-1.78) [49].…”
Section: Aspirinmentioning
confidence: 99%